Novel chiral stationary phases based on 3, 5‐dimethyl phenylcarbamoylated β‐cyclodextrin combining cinchona alkaloid moiety. Issue 8 (8th May 2020) - Zhu, Lunan; Zhu, Junchen; Sun, Xiaotong; Wu, Yaling; Wang, Huiying; Cheng, Lingping; Shen, Jiawei; Ke, Yanxiong
Abstract: Novel chiral selectors based on 3, 5‐dimethyl phenylcarbamoylated β‐cyclodextrin connecting quinine (QN) or quinidine (QD) moiety were synthesized and immobilized on silica gel. Their chromatographic performances were investigated by comparing to the 3, 5‐dimethyl phenylcarbamoylated β‐cyclodextrin (β‐CD) chiral stationary phase (CSP) and 9‐ O ‐( tert ‐butylcarbamoyl)‐QN‐based CSP (QN‐AX). Fmoc‐protected amino acids, chiral drug cloprostenol (which has been successfully employed in veterinary medicine), and neutral chiral analytes were evaluated on CSPs, and the results showed that the novel CSPs characterized as both enantioseparation capabilities of CD‐based CSP and QN/QD‐based CSPs have broader application range than β‐CD‐based CSP or QN/QD‐based CSPs. It was found that QN/QD moieties play a dominant role in the overall enantioseparation process of Fmoc‐amino acids accompanied by the synergistic effect of β‐CD moiety, which lead to the different enantioseparation of β‐CD‐QN‐based CSP and β‐CD‐QD‐based CSP. Furthermore, new CSPs retain extraordinary enantioseparation of cyclodextrin‐based CSP for some neutral analytes on normal phase and even exhibit better enantioseparation than the corresponding β‐CD‐based CSP for certain samples. Abstract : 1. Preparation of novel β‐CD‐based CSPs with cinchona alkaloid moiety. 2. Extending application spectrum by introducing QN/QD moiety. 3. Enantioselectivities on CSPs in a structure‐dependent manner.